(untitled) (Journal of the College of Basic Education, 2023)
The aim of the current research is to identify (statistical thinking skills included in the mathematics textbook for the third intermediate grade (C1, C2) for the academic year 2021-2022 AD. All topics related to statistics included in the third intermediate grade mathematics book (C1, C2) for the academic year (2021-2022 AD), and the current research adopted the idea unit (explicit, implicit) as a unit of analysis, and repetitions as a unit of counting, and to achieve the goal of the research, the researcher built an initial list of skills Statistical thinking, and the apparent validity of the tool was confirmed by presenting it to the arbitrators, and the final list included (40) indicators and (26) sub-skills distributed on (4) major skills for statistical thinking. ) by using the content analysis tool (statistical thinking skills), and the validity of the analysis and the stability of the analysis were verified by the two methods over time (the researcher with herself after a certain period of time), and across others. (The researcher with other analysts), and calculating the percentage of agreement using the Holsti equation, and the researcher used Cooper’s equation, frequencies and percentages as statistical means, and the research reached the most important results, the most important of which is that the third grade mathematics book (C1, C2) included all of the concepts Statistical studies, but in varying proportions, and in an unbalanced manner, and recommendations were made, including: (observing balance when including statistical thinking skills in the content of the third intermediate grade mathematics book (C1, C2), in proportion to the scientific level of the subject, and taking into account the diversity and diversity in the choices), She suggested conducting analytical studies of preparatory school mathematics books according to statistical thinking skills and the extent to which students have acquired them